43.6k views
4 votes
Find the error and show the correct solution.

1
5x –9 = -2(x-3)
5x-9 = -2x + 5
7x = 14
x = 2

1 Answer

6 votes

15/7

Explanation:

The error is in :


- 2(x - 3)

It was expanded as -2x +5 which was wrong

Correct solution


5x - 9 = - 2(x - 3) \\ 5x - 9 = - 2x + 6 \\ 5x + 2x = 6 + 9 \\ 7x = 15


(7x)/(7) = (15)/(7) \\ \\ x = 2 (1)/(7)

User Paras Watts
by
4.9k points
Welcome to QAmmunity.org, where you can ask questions and receive answers from other members of our community.